Optical properties of spray pyrolysis deposited Cds:Al thin films (Journal of Bangladesh Academy of Sciences, 2015)
Aluminium doped cadmium sulphide thin films were prepared on glass substrate using aqueous solution of cadmium sulphide and thiourea salts by spray pyrolysis deposition (SPD) technique. Its optical properties were analyzed as a function of doping concentration. The direct energy band-gap of Al-doped CdS films was estimated in the range of 2.25 to 2.48 eV. The optical spectra of Cd1-xAlxS ternary system exhibit high absorption near visible region and transmission throughout the near-infrared region (600 - 1200 nm). Thus so obtained hetero-junction films are suitable for fabrication of photo detectors, solar cells and other optoelectronics devices.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 25-30, 2015